VALIDASI INSTRUMEN FOLLOWERSHIP MODEL KELLEY VERSI INDONESIA - Rosani, Siti Asriyani; Tarigan, Medianta (JURNAL PSIKOLOGI INSIGHT, 2019)
This study aimed to describe the psychometric properties of the Followership measurement. The participants of the research were 377 of employees with range of 16 - 59 years old. The research used internal consistency of Alpha and construct validity with Confirmatory Factor Analysis (CFA), convergent validity, and discriminant validity. The results were high internal consistency reliability of Indonesian Kelly’s followership styles (α = 0.882), and good fit indexes of modified two factor model (activity and independent), and finally showed the positive correlation to ledadership, work engagement, and religiosity measures.